Attentional Capture to a Singleton Distractor Degrades Visual Marking in Visual Search - Yamauchi, Kenji; Osugi, Takayuki; Murakami, Ikuya (Frontiers in Psychology, 2017)
Visual search is easier after observing some distractors in advance; it is as if the previewed distractors were excluded from the search. This effect is referred to as the preview benefit, and a memory template that visually marks the old locations of the distractors is thought to help in prioritizing the locations of newly presented items. One remaining question is whether the presence of a conspicuous item during the sequential shift of attention within the new items reduces this preview benefit. To address this issue, we combined the above preview search and a conventional visual search paradigm using a singleton distractor and examined whether the search performance was affected by the presence of the singleton. The results showed that the slope of reaction time as a function of set size became steeper in the presence of a singleton, indicating that the singleton distractor reduced the preview benefit. Furthermore, this degradation effect was positively correlated with the degree of conventional attentional capture to a singleton measured in a separate experiment with simultaneous search. These findings suggest that the mechanism of visual marking shares common attentional resources with the search process.